The case of the perfect prank - Preller, James; Smith, Jamie; Alley, R. W. (Robert W.) (New York : Scholastic Inc., 2004)
Jigsaw's brothers love to play practical jokes. But Jigsaw does not have time for games. He has a big case to solve. Danika's kitty has been cat-napped. Can Jigsaw solve the mystery? Or will the cat burglar have the last laugh?
"A Little Apple paperback."
G2
Keywords: Mystery and detective stories